Evaluation of different fungicides for the control of Alternaria leaf spot of roses caused by “Alternaria alternata” (Plant Bulletin, 2022)
Rose (Rosa indica L) is important plant uses worldwide in medical, cosmetic, happy events, celebrations and food tonic supplement. Fungal diseases (powedery mildew, anthracnose, rust, root rots, Alternaria black spot, cercospora leaf spot and grey mold) are well known for threat to cultivation of rose plant for commercial scale. Among them Alternaria black spot disease is the most dangerous one. Present study was done in the field area of College of Agriculture, Bhadur sub. campus Layyah in 2019 using RCBD 3 factorial design. The study was carried out to evaluate and to check efficacy of five fungicides (Ridomil Gold, Companion, Acrobat MZ, Dodine and Myclobutanil) to control the disease at different concentration and days. Results indicate that disease is effectively controlled by Ridomil Gold (17.68%) followed by Acrobat MZ (24.35%), Myclobutanil (34.69%), Companion (49.72%) while Dodine showed least efficacy (44.84%) over control (73.54 %). Ridomil gold can be used to control Alternaria black spot of rose.
Keywords: Rose leaf spot; Alternaria alternata; Alternaria leaf spot; Fungicide; chemical treatment